Protocol of the OPTIMAL study: optimization of polypharmacy in geriatric oncology - a randomized controlled trial - Schöttker, Ben; Chen, Li-Ju; Caspari, Reiner; Brenner, Hermann (BMC cancer, 2023)
Background: Polypharmacy is very common in older cancer patients and these patients are particularly vulnerable to drug-drug interactions and adverse drug reactions because they often receive chemotherapy and symptom-relieving agents. Methods: The primary aim of the randomized, controlled Optimization of Polypharmacy in Geriatric Oncology (OPTIMAL) trial is to test whether an advisory letter with the results of a comprehensive medication review conducted with the Fit fOR The Aged (FORTA) list to the caring physician in rehabilitation clinics improves the quality of life (QoL) of older cancer patients exposed to polypharmacy more than usual care. The FORTA list detects medication overuse, underuse, and potentially inappropriate drug use among older adults. In the oncology departments of approximately 10 German rehabilitation clinics, we aim to recruit 514 cancer patients (22 common cancers; diagnosis or recurrence requiring treatment in the last 5 years; all stages) who are ≥ 65 years old, regularly take ≥ 5 drugs, and have ≥ 1 medication-related problem. All necessary information about the patients will be provided to a pharmacist at the coordinating center (German Cancer Research Center, Heidelberg), who will perform randomization (1:1) and conduct the medication review with the FORTA list. For the intervention group only, the results are sent by letter to the treating physician in the rehabilitation clinics, who shall discuss medication changes with the patient at the discharge visit, as well as implement them afterwards and disclose them in the discharge letter to the general practitioner. The control group gets the usual care provided in German rehabilitation clinics, which usually does not include a comprehensive medication review but can include medication changes. Patients will be blinded, as they cannot know whether proposed medication changes were part of the study or part of usual care. Study physicians cannot be blinded. The primary endpoint will be the EORTC-QLQ-C30 global health status/QoL score, assessed via self-administered questionnaires 8 months after baseline. Discussion: If the planned study shows that a medication review with the FORTA list improves the QoL of older cancer patients in oncological rehabilitation more than usual care, it would provide the necessary evidence to translate the trial’s findings into routine care.
Gesehen am 12.06.2023